GERMINAÇAO DE SEMENTES DE Combretum leprosum MART. - MAURO VASCONCELOS PACHECO; FERNANDO DOS SANTOS ARAÚJO; CIBELE DOS SANTOS FERRARI; RISELANE DE LUCENA ALCÂNTARA BRUNO (Revista Caatinga, 2014)
Combretum leprosum Mart. is a tree species native of the Caatinga, used in the restoration of degraded areas and in folk medicine. Thus, this research aimed to evaluate the germination and vigor of the seeds subjecting them to different pre-germinative treatments, temperatures and substrates. In the first experi- ment, we tested the pre-germinative treatments: mechanical scarification with sandpaper, chemical scarification with H2SO4 for 1, 5, 10 and 20 minutes, immersion in water at 80 oC and imbibition in distilled water for 24 hours, beyond of the control. In the second experiment, after treatment of imbibition in water for 24 hours, the experimental design was completely randomized in a factorial 5 x 4 (five substrates: into paper, sand, coconut fiber, vermiculite and paper towel organized in the form of rolls; and four temperatures: 25, 30, 35 and 20-30 oC). The following parameters were evalueted: seed moisture content, germination, germination speed index, first germination count and seedling length and dry matter weight. The seeds of Combretum leprosum have not coat dormancy. However, pre-germinative treatments of mechanical scarification with sandpaper and imbibi- tion in water for 24 hours allows better expression of seeds vigor. The paper towel and the temperatures of 25, 30 and 20-30 oC provide adequate conditions for evaluating the germination of Combretum leprosum seeds.